THE EFFECT OF COMPENSATION, WORK ENVIRONMENT, AND CAREER DEVELOPMENT ON EMPLOYEE LOYALTY (Study on Bank Jateng Syariah Employees) - Firlian Fikri Egyansyah; Akhmad Darmawan; Wida Purwidianti; Purnadi Purnadi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to determine the effect of Compensation, Work Environment, and Career Development on Employee Loyalty. This research is a quantitative research with the data source used namely primary data. The population and sample used in this study were employees of Bank Jateng Syariah Purwokerto Branch Office, Semarang Branch Office, and Sharia Division using a saturated sample method of 102 employees of Bank Jateng Syariah. Data collection techniques using questionnaires distributed directly to employees. The data analysis method used is Multiple Regression Analysis using the Stata 17 application. The results of this study indicate that (1) Compensation, Work Environment, and Career Development simultaneously have a positive and significant effect on Employee Loyalty, (2) Compensation has a positive and significant effect on Employee Loyalty. Employee Loyalty, (3) Work Environment has a positive and significant effect on Employee Loyalty, and (4) Career Development has a positive and significant effect on Employee Loyalty.